Pengaruh Kepemimpinan Kepala Sekolah dan Partisipasi Komite Sekolah Terhadap Kinerja Guru Serta Dampaknya Pada Prestasi Belajar Siswa - Suarni Norawati; Budi Hermanto; Zamhir Basem; Supardi Supardi (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This research was conducted at SMP Negeri 8 Pinggir with the aim of finding out the influence between the principal's leadership and school committee participation on teacher performance and its impact on student learning achievement. The population in this study was 32 teachers and the sample was determined using a saturated census technique so that the total sample in this study was 32 respondents. The data analysis technique uses Structural Equation Modeling (SEM) using SmartPLS version 3.0 software. The results of the research show that the principal's leadership has a significant direct effect on teacher performance, school committee participation has a direct significant effect on teacher performance, the principal's leadership has a significant direct effect on student learning achievement, school committee participation has a direct significant effect on student learning achievement, Teacher performance has a significant direct effect on student learning achievement, principal leadership has a significant indirect effect on student learning achievement through teacher performance, and school committee participation has a significant indirect effect on student learning achievement through teacher performance